Influência da adição de Nb, Ti e Zr nas propriedades de fluência da liga HP fundida por centrifugação - Andrade, Antonio Rafael de (2014)
This work aimed to evaluate the influence caused by Nb single addition and by Nb-Ti and Nb-Zr combined addition in the high temperature mechanical properties of a centrifugally cast HP alloy. Particular investigation was carried out on creep and hot tensile properties in the temperature range between 900 to 1100 oC. Seamless tubes were casted by horizontal centrifugal process with the following nominal composition 0.50C-25Cr-35Ni, 0.50C-25Cr-35Ni-1Nb, 0.50C- 25Cr-35Ni-1Nb-0.1Ti e 0.50C-25Cr-35Ni-1Nb-0.1Zr. These 04 alloys were evaluated using the following techniques differential scanning calorimetry (DSC), optical and electron microscopy, energy dispersive spectroscopy (EDS) and X-ray diffraction (XRD). The mechanical characterization was performed by elevated temperature tension tests with 3 different strain rates and constant load creep rupture test in the stress range of 65 to 15 MPa and comprising rupture times between 10 to 2000 hours, with or without extensometer using. The results were interpreted using classical methodologies (Norton, Arrhenius, Monkman-Grant, Larson-Miller, and others). The results shown that these elements addition did not change significantly the macrostructure, but they played an important role on formation, fragmentation, size, quantity, distribution, coarsening and coalescence on the carbides in the microstructure. Additions also refined the dendritic arm space. These microstructural changes led to a different mechanical behavior in each alloy. In the elevated temperature tension tests the Nb addition led to the highest values for mechanical resistance. On the other hand, Nb-Ti and Nb-Zr addition presented the highest time to rupture in creep tests, but in opposite conditions of temperature and stress.